Improved detection of erosions in the sacroiliac joints on MRI with volumetric interpolated breath-hold examination (VIBE): results from the SIMACT study. Issue 11 (10th August 2018) - Diekhoff, Torsten; Greese, Juliane; Sieper, Joachim; Poddubnyy, Denis; Hamm, Bernd; Hermann, Kay-Geert A
Abstract : Objective: To compare the performance of a new three-dimensional MRI sequence (volumetric interpolated breath-hold examination; MR-VIBE) with a conventional T1-weighted sequence (MR-T1) for the detection of erosions in the sacroiliac joints (SIJs) using low-dose CT (ldCT) as reference. Methods: ldCT and T1-MRI and MR-VIBE of 110 prospectively included patients with low back pain and suspected axial spondyloarthritis (axSpA) were scored for erosions by two readers. The presence of erosions on the patients' level, the erosion sum score, sensitivity and specificity of both MRI sequences using ldCT as a reference as well as agreement between the readers were assessed. Results: MR-VIBE had a higher sensitivity than MR-T1 (95% vs 79%, respectively) without a decrease in specificity (93% each). MR-VIBE compared with MR-T1 identified 16% more patients with erosions (36 vs 30 of 38 patients with positive ldCT findings). The erosion sum score was also higher for MR-VIBE (8.1±9.3) than MR-T1 (6.7±8.4), p=0.003. The agreement on erosion detection was also higher for MR-VIBE (κ=0.71) compared with MRI-T1 (κ=0.56). Conclusion: VIBE detected erosions in the SIJs with higher sensitivity without a loss of specificity and superior reliability compared with a standard T1-weighted sequence. Its value for the diagnosis of axSpA has still to be determined.